Importance of Early Weight Change in a Pediatric Weight Management Trial - Goldschmidt, Andrea B. (American Academy of Pediatrics, 2011)
OBJECTIVE: Early weight change is associated with overall weight loss treatment response in adults but has been relatively unexplored in youth. We investigated the importance of early weight change in a pediatric weight control trial. METHODS: Overweight children aged 7 to 12 years (n = 204) participated in a randomized controlled trial of 2 weight maintenance treatments (MTs) after a 20-week family-based behavioral weight loss treatment (FBT). Hierarchical regression was used to investigate the relation between children's percentage weight change at sessions 4, 6, and 8 of FBT and BMI z-score reductions after FBT and at the 2-year follow-up. Correlations and hierarchical regression were used to identify child and parent factors associated with children's early weight change. RESULTS: Children's percentage weight change by FBT session 8 was the best predictor of BMI z-score reductions after FBT and at 2-year follow-up. Percentage weight change in children at the session 8 was associated with better FBT attendance and with greater percentage weight change in parents at FBT session 8. CONCLUSIONS: Early weight change seems to be related to treatment response through the end of treatment and 2-year follow-up. Future research should include investigation of strategies to promote early weight change in children and parents and identification of mechanisms through which early weight change is related to overall treatment response.